Apakah Modifikasi Alat Bantu Pembelajaran Penjas dapat Meningkatkan Self Esteem Siswa? - gita febria friskawati (Journal of Sport Science and Education, 2017)
The purpose of the study is to reveal the effect of physical education learning tools modification on student self esteem. Eksperimental with Pretest-Posttest Control Group Desain is used in this research.Eksperimental conducted in population of senior high school with a total 328 people. Group A consist of 42 people and group B consist of 38 people that taken cluster random sampling. This research conducted over 8 times the meeting. After overall data is tested using paired t-test test, the results show that thesignificance value of 0.039 <0.05 at group using physical education learning tools modification, means Ho rejected and 0794 <0.05 in the group not using physical education learning tools modification, means that Ho is accepted. So, the results is using physical education learning tools modification can improve student self esteem. The implication is expected to teacher to using physical education learning tools modification for Students increases self-esteem in physical education teaching learning.